REPRESENTASI GIRL POWER PADA LAGU “TALLY” OLEH BLACKPINK - Fatonah, Astri Amaliah; Handayani, Wiwik Retno (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2024)
A patriarchal culture dominated the representation of social reality, resulting in women's victimization. However, now the media is highlighting women in terms of educational achievements, so the existence of independent women is increasing. This research aims to discuss the representation of Girl Power shown in the video clip and lyrics of the song